The correlation between provision time of weaning food and history of exclusive breastfeeding with nutritional status in toddlers - Mulyaningsih, Sundari; Fatimah, Fatimah; Paramita, Dyah Pradnya; Supiyati, Supiyati; Susilowati, Ika Tri; Mirnasari, Nicwa; Delia, Amanah Rahma (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: The toddler period is a golden age for the formation and development of children starting from the basic sensory abilities, thinking, speaking, and intensive intellectual mental growth and early moral growth. So that the nutritional status of children under five is very, very important to study because it is related to the current increasing stunting status. Cases of stunting under five currently have the highest number when compared to other forms of malnutrition. The prevalence of stunting in DIY in 2018 was 12.37% and this figure fell to 10.69% in 2019 but in 2020 it rose to 11.08%. The highest prevalence of stunting is Gunung Kidul Regency (17.43) and the lowest is Sleman Regency (7.24). From this figure, it can be seen that the prevalence of very short toddlers in DIY is lower when compared to Riskesdas in 2018 (21.4%) (1). Objectives: To determine the relationship between the characteristics (education, occupation) of the mother, provision time of weaning food, exclusive breastfeeding, and the provision of deworming drugs with nutritional status in toddlers aged 6-60 months in 2 areas, namely in the work area of the Pajangan Health Center and the Work Area of the Public Health Center, Sedayu. Methods: Analytic survey with cross-sectional design. Analysis of the data using the chi-square test with a sample of 35 mothers who have children under five. Results: The results showed that there was a correlation between the time of weaning food (p = 0.0001), history of exclusive breastfeeding (p = 0.0001), and the nutritional status of children under five. However, there was no correlation between education (p = 0.657), occupation (p = 0.579), deworming (p = 0.410). Conclusions: There is a correlation between the time of weaning food, history of exclusive breastfeeding nutritional status in toddlers